Evaluation and Analysis of the Level of Political Awareness about FATF - Ali Bagheri Dolatabadi (رهیافتهای سیاسی و بین المللی)
The purpose of this study is to investigate the political awareness of the students of Yasouj University about the Financial Action Task Force (FATF) and related conventions and also factors affecting their knowledge. Research hypothesis emphasizes students› awareness of the subject of research. A survey method was used to measure this issue. Using the Cochran formula, the sample size was 400 people and 24 Closed questions were given to them. The questionnaire consisted of 4 sections and each section had 6 questions about the United Nations Conventions on Combating the Financing of Terrorism, the United Nations Convention against Transnational Organized Crime, the United Nations Convention against Corruption and the Financial Action Task Force (FATF). The findings showed that the students› political awareness was moderate. The most political awareness belonged to FATF and the least political awareness was about the United Nations Convention against Corruption. Also, male students compared to girls and students of humanities faculty compared to other faculties had more political awareness. In addition, there was a significant correlation between student›s political awareness with age and media consumption, but there was no relationship between the two variables of household economic status and the student›s residence.